2022
DOI: 10.1002/jgm.3447
|View full text |Cite
|
Sign up to set email alerts
|

Potentially functional genetic variants of VAV2 and PSMA4 in the immune‐activation pathway and non‐small cell lung cancer survival

Abstract: Background: Lung cancer has the highest mortality among cancers, represented by a low 5-year survival rate. The function of the immune system has a profound influence on the development and progression of lung cancer. Thus genetic variants of the immune-related genes may serve as potential predictors of non-small cell lung cancer (NSCLC) survival. Methods:In the present study, we conducted a two-stage survival analysis in 1,531 NSCLC patients and assessed the associations between genetic variants in the immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Additionally, PGK1 is linked to cancer patients' poor prognoses and resistance to chemotherapy and radiation therapy. According to Yushun Bai et al 62 , PSMA4 may influence lung cancer OS via cis-regulating the expression of the relevant genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PGK1 is linked to cancer patients' poor prognoses and resistance to chemotherapy and radiation therapy. According to Yushun Bai et al 62 , PSMA4 may influence lung cancer OS via cis-regulating the expression of the relevant genes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PGK1 is linked to cancer patients' poor prognoses and resistance to chemotherapy and radiation therapy. According to Yushun Bai et al [62], PSMA4 may influence lung cancer OS via cis-regulating the expression of the relevant genes. LY96 was shown to be considerably increased by Kechao Nie et al [63] in the majority of cancers, and their findings revealed that LY96 was connected to cancer copy number, DNA methylation, somatic mutation, microsatellite instability, tumor mutation load, and tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…These results could explain why central MG and RGCs are more resistant to HP than the peripheral cells. Among the proteins overexpressed in peripheral MG under exposed to HP as opposed to the control peripheral MG are: ACTN4, a member of the actin binding protein family that interacts with DNaseY and mediates DNA fragmentation during apoptosis [66]; Epha2, from the Eph receptor tyrosine kinase (RTK) family, the largest group of tyrosine kinases in the genome [67], an RTK regulated by p53 proteins that induces apoptosis [68]; FABP3, member of a family of binding proteins that inhibits proliferation and promotes apoptosis when overexpressed [69]; TXN is a key element in the elimination of reactive oxygen species [70]; and PSMA4 that interacts with proteins with a strong immune response [71]. The increase in the proportion of proteins related to these functions suggests that the peripheral MG are more sensitive to HP, and consequently they negatively affect the survival of RGCs and of themselves.…”
Section: Discussionmentioning
confidence: 99%